2013
DOI: 10.5897/ajb12.2297
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparative effect of extracts of the seeds of Embelia rowlandii (Myrsinaceae) on the eggs and L1 and L2 larval stages of the parasitic nematode Heligmosomoides bakeri (Nematoda; Heligmosomatidae)

Abstract: In vitro ovicidal and larvicidal activities of extracts of the seeds of Embelia rowlandii were investigated on unembryonated and embryonated eggs, first and second stage larvae of Heligmosomoides bakeri. Three different extracts were prepared with distilled water (DW) and 95% ethanol. The organic extract was first diluted with 3% Tween and then distilled water added to obtain five different concentrations (625, 1250, 2500, 3750 and 5000 µg/ml). These concentrations were put in contact with eggs and larvae of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
4
2
0
Order By: Relevance
“…Similar observations were made by Payne et al [ 32 ]. According to Payne et al [ 32 ], the active compounds found in the extracts may paralyze the larvae by blocking the post-synaptic receptors.…”
Section: Discussionsupporting
confidence: 92%
“…Similar observations were made by Payne et al [ 32 ]. According to Payne et al [ 32 ], the active compounds found in the extracts may paralyze the larvae by blocking the post-synaptic receptors.…”
Section: Discussionsupporting
confidence: 92%
“…Te larvicidal properties of these extracts may be due to the penetration of active compounds across the cuticle of the larvae on one hand or the absorption of the substance by the larvae. Tis fnding is similar to that obtained by Payne [23]. Payne [23] mentioned that active compounds penetrate the cuticle of nematodes and prevent the absorption of glucose or block postsynaptic receptors, thus paralyzing the larvae.…”
Section: Discussionsupporting
confidence: 75%
“…Tis fnding is similar to that obtained by Payne [23]. Payne [23] mentioned that active compounds penetrate the cuticle of nematodes and prevent the absorption of glucose or block postsynaptic receptors, thus paralyzing the larvae. Te active compound may inhibit the transmission of nervous impulses by gamma-aminobutyric acid (GABA) whose secretion is stimulated by the active compound [23].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The larvicidal activity and adult mortality observed in our results may be due to the penetration of active phytochemicals through the cuticle of larvae and adult worms [43]. According to [44], the effect of tannins is similar to that of certain synthetic phenolic anthelmintics such as niclosamide and nitroxynil, which interfere with energy production by decoupling oxidative phosphorylation in parasitic helminths.…”
Section: Discussionmentioning
confidence: 62%